PREBIOTIC EFFECT OF LACTULOSE AMONG INFANTS - L.A. Nikulin; L.M. Kravchenko; E.P. Apalkova ("Paediatrician" Publishers LLC, 2007)
The article demonstrates the modern viewpoint on the functional feeding of the infants. The researchers give the application findings in respect of lactulose (Normase) - a medication with prebiotic effect, among children, undergoing artificial feeding. It is showed that lactulose improves bowels micro-biocenosis and contributes to symptoms couping of the digestion disorders. The medication is recommended by the authors as a prebiotic for the newborns deprived of the mother's milk.Key words: children, micro-biocenosis, lactulose, prebiotic.